Chemical Risk Assessment At The International Programme On Chemical Safety - A. Aitio (The Southern African Institute of Mining and Metallurgy, 2004)
Sustainable development is one of the central themes of the work of the World Health Organization; chemical safety is one of its important components. For more than 25 years, WHO has had specialized units for assisting member countries in dealing with their problems in chemical safety. For one of the units involved, International Programme on Chemical Safety, a reorientation is in progress to make best use of existing resources, and to prioritise the work to optimally correspond to the needs of the member countries. The risk assessment work of IPCS, and specifically, the work on chromium and chromium compounds, are discussed.